50-plus years of fungal viruses - Ghabrial, Said A.; Castón, José R.; Jiang, Daohong; Nibert, Max L.; Suzuki, Nobuhiro (Virology (New York, N.Y.), 2015)
Mycoviruses are widespread in all major taxa of fungi. They are transmitted intracellularly during cell division, sporogenesis, and/or cell-to-cell fusion (hyphal anastomosis), and thus their life cycles generally lack an extracellular phase. Their natural host ranges are limited to individuals within the same or closely related vegetative compatibility groups, although recent advances have established expanded experimental host ranges for some mycoviruses. Most known mycoviruses have dsRNA genomes packaged in isometric particles, but an increasing number of positive- or negative-strand ssRNA and ssDNA viruses have been isolated and characterized. Although many mycoviruses do not have marked effects on their hosts, those that reduce the virulence of their phytopathogenic fungal hosts are of considerable interest for development of novel biocontrol strategies. Mycoviruses that infect endophytic fungi and those that encode killer toxins are also of special interest. Structural analyses of mycoviruses have promoted better understanding of virus assembly, function, and evolution. •Historical perspective of fungal virus research.•Description, classification and diversity of fungal virus families.•Structural features of fungal virus particles.•Hypovirulence and exploitation of mycoviruses in biological control of plant pathogenic fungi.